A case of dengue-related osteonecrosis of the maxillary dentoalveolar bone - Al-Namnam, N.M.; Nambiar, P.; Shanmuhasuntharam, P.; Harris, M. (Wiley, 2017)
Dengue is a mosquito transmitted flaviviral infection which can give rise to severe haemorrhage (dengue haemorrhagic fever) and with capillary leakage induces hypovolaemic shock (dengue shock syndrome). Although dengue symptoms and complications have been known for many decades, there has only been one documented case of osteonecrosis of the maxilla which was treated by excision of the necrotic bone. In this case of dengue infection, extensive maxillary osteonecrosis and minimal root resorption appeared to follow factitious injury with a toothpick but resolved with nonsurgical management.